2008
DOI: 10.1016/j.molbiopara.2007.10.009
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference of Schistosoma mansoni cathepsin D, the apical enzyme of the hemoglobin proteolysis cascade

Abstract: The aspartic protease cathepsin D (Clan AA, Family A1) is expressed in the schistosome gut where it plays an apical role in the digestion of hemoglobin released from ingested erythrocytes. In this report, RNA interference approaches were employed to investigate the effects of knockdown of schistosome cathepsin D. Cultured schistosomules of Schistosoma mansoni were exposed by square wave electroporation to double stranded RNA (dsRNA) specific for cDNA encoding S. mansoni cathepsin D. RNAi mediated reductions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(121 citation statements)
references
References 37 publications
5
114
0
2
Order By: Relevance
“…By silencing the expression of the Sm-catD gene, Morales et al 14 showed that Sm-CatD is the only enzyme in the schistosome that is capable of cleaving MoCAc-GKPILFFRLK at low pH. We therefore concluded herein that anti-LCP-2 IgG mediated inhibition of proteolytic cleavage of this peptide substrate by schistosome somatic extracts provided strong evidence that these antibodies were indeed enzyme-neutralizing, and would therefore potentially interrupt digestion of the schistosome's bloodmeal.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…By silencing the expression of the Sm-catD gene, Morales et al 14 showed that Sm-CatD is the only enzyme in the schistosome that is capable of cleaving MoCAc-GKPILFFRLK at low pH. We therefore concluded herein that anti-LCP-2 IgG mediated inhibition of proteolytic cleavage of this peptide substrate by schistosome somatic extracts provided strong evidence that these antibodies were indeed enzyme-neutralizing, and would therefore potentially interrupt digestion of the schistosome's bloodmeal.…”
Section: Discussionmentioning
confidence: 58%
“…13 RNA interference targeting the gene encoding S. mansoni CatD resulted in a lethal phenotype (growth retardation) and the reduction in the ability of the parasite to effectively digest Hb in vitro. 14 While it is possible to generate recombinant Sm-CatD for small-scale vaccine testing, high-yield expression of eukaryotic proteases is problematic. 15,16 Moreover, the most efficacious vaccines for helminth infections are likely to require multiple antigens or fragments thereof, and must induce high titer antibody responses that are long-lasting.…”
Section: Introductionmentioning
confidence: 99%
“…The RNAi approach was already used in several areas of S. mansoni biology (Boyle et al 2003, Skelly et al 2003, Correnti et al 2005, Delcroix et al 2006, Dinguirard and Yoshino 2006, Freitas et al 2007, Krautz-Peterson and Skelly 2008b, Morales et al 2008, Pereira et al 2008, Faghiri and Skelly 2009, Rinaldi et al 2009, Beckmann et al 2010 as well as in S. japonicum (Cheng et al 2005, Zhao et al 2008, Kumagai et al 2009. RNAi has proved itself as an important tool to elucidate gene function in schistosomes, in a similar way as in other organisms.…”
Section: Short Non-coding Rnasmentioning
confidence: 99%
“…Schistosome cathepsin D is involved in haemoglobin digestion, a process that provides the parasite with its main source of amino acid nutrients and that is essential for its development, growth and reproduction (Brindley et al 2001, Caffrey et al 2004, Delcroix et al 2006. Given the essential function of cathepsin D in parasite nutrition and the ability of recombinant forms to cleave human immunoglobulin G, this protein is considered a potential target for novel anti-parasitic interventions (Verity et al 2001, Morales et al 2008.…”
Section: Endopeptidase Family Members Are Duplicated In Smentioning
confidence: 99%
“…Schistosome cathepsin D is involved in haemoglobin digestion, a process that provides the parasite with its main source of amino acid nutrients and that is essential for its development, growth and reproduction (Brindley et al 2001, Caffrey et al 2004, Delcroix et al 2006. Given the essential function of cathepsin D in parasite nutrition and the ability of recombinant forms to cleave human immunoglobulin G, this protein is considered a potential target for novel anti-parasitic interventions (Verity et al 2001, Morales et al 2008.The phylogenetic relationships of each endopeptidase family (Figs 2-4) are shown with protein sequences represented by identifiers in PhylomeDB (phylomedb. org) (Huerta-Cepas et al 2011), UniProt (uniprot.org) (Apweiler et al 2011) and/or SchistoDB (schistodb.net) (Zerlotini et al 2009).…”
mentioning
confidence: 99%